2009
DOI: 10.1111/j.1752-9824.2009.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of pain control by consumers with chronic kidney disease

Abstract: Aims and objectives.  This study investigated the perceptions of consumers with chronic kidney disease in relation to their pain control, the barriers and enablers to effective pain control, and how they made decisions in relation to their pain control. Background.  Consumers with chronic kidney disease are likely to experience pain as a consequence of their kidney disease, comorbidities, treatment and complications which is in need of investigation. Methods.  Twenty consumers were recruited from two metropoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Renal Data System, 2017). Pain is a significant problem in more than half of individuals undergoing hemodialysis and is not being adequately controlled, with many people describing ineffective pain management (Claxton, Blackhall, Weisbord, & Holley, 2010; Davison, 2003; Williams & Manias, 2009). Davison and Jhangri (2005) established a relationship between depressive symptoms and chronic pain, finding that 55% ( n = 205) of individuals receiving hemodialysis reported pain interfered with their mood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Renal Data System, 2017). Pain is a significant problem in more than half of individuals undergoing hemodialysis and is not being adequately controlled, with many people describing ineffective pain management (Claxton, Blackhall, Weisbord, & Holley, 2010; Davison, 2003; Williams & Manias, 2009). Davison and Jhangri (2005) established a relationship between depressive symptoms and chronic pain, finding that 55% ( n = 205) of individuals receiving hemodialysis reported pain interfered with their mood.…”
mentioning
confidence: 99%
“…They also reported that pain, fatigue, and decreased well-being accounted for almost 39% of physical health composite scores on the Kidney Dialysis Quality of Life Short Form (Davison & Jhangri, 2010). The etiology of this pain may be from numerous causes; it can be the result of concurrent comorbidities such as diabetes and vascular disease, or venipunctures and muscle cramping during the hemodialysis treatment itself (Davison, 2003; Williams & Manias, 2009). Although inadequate symptom management is not unique to nephrology, managing pain in the hemodialysis population poses unique challenges due to medication biproducts and renal clearance (Bailie, Mason, Bragg-Gresham, Gillespie, & Young, 2004; Davison, 2003).…”
mentioning
confidence: 99%